2014
DOI: 10.5539/jas.v6n7p253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Maize Input Subsidy Program on Groundnuts Production in Zambia

Abstract: This study uses a three-wave panel dataset from nationally representative surveys by the Central Statistical Office and Cragg's (1971) model for corner-solution problems to determine the effect of the government-sponsored maize input subsidy program on the production of groundnuts in Zambia. The results show that even though the maize subsidy programme, does not significantly affect the smallholder farmer's decision to participate in groundnuts production, maize subsidies however do significantly influence the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In Kenya, Mason et al (2017) reported a land allocation bias toward maize as a result of fertiliser and improved seed subsidy programmes that targeted maize. Mason et al (2013) and Zulu et al (2014) examined the effect of the maize input subsidy programme (fertiliser and improved seed) on a legume crop. They found that farmers reallocate land toward maize from other crops like groundnuts.…”
Section: Introductionmentioning
confidence: 99%
“…In Kenya, Mason et al (2017) reported a land allocation bias toward maize as a result of fertiliser and improved seed subsidy programmes that targeted maize. Mason et al (2013) and Zulu et al (2014) examined the effect of the maize input subsidy programme (fertiliser and improved seed) on a legume crop. They found that farmers reallocate land toward maize from other crops like groundnuts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as a result of reduced dependence on maize imports, the carbon footprint (Chinsinga, 2011). However, there has been some evidence from neighbouring Zambia of similar input subsidy programmes resulting in reductions in area allocated to non-cereal crop production and negative impacts on production diversity (Zulu et al, 2014, Chinsinga, 2011. Concerns have also been raised in relation to subsidy programmes about the sustainability of agricultural inputs (e.g.…”
mentioning
confidence: 99%